STAGING AND PERFORMING IDENTITY AT THE CROKE PARK CLASSIC: A NOTE ON SPORT, GEOGRAPHY AND NEOLIBERALISM - Nicholas WISE (European Journal of Geography)
American Football has seen limited success in international markets until recently. This paper is based on participant observations that incorporate a geographical perspective of sport and identity focusing on an American Football event played in Dublin, Ireland. The aim of this paper is to discuss observations of how a popular American sport is staged and performed in a foreign setting. Many people from the United States travelled to Dublin to follow their university team. The event was staged to allow spectators to create a distinct atmosphere that was similar to a game played in the United States. There was much emphasis on (re)creating an American sporting experience. The match resembled a spectacle and a neoliberal discussion addresses commercialization, power, and contesting spaces.